المقارنة بين كفاءتي النظام الفصلي الحالي والفصلي المعدل من خلال نسبة ترفع(انتقال) الطلاب من سنة دراسية الى سنة اعلى- مثال كلية الاقتصاد بجامعة تشرين - عكروش, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
باعتبار أن العملية التعليمية هي منظومة من العمليات التي تترابط مع بعضها البعض وتشارك في حدوثها مجموعة من العوامل, تؤثر وتتأثر بها ولكل منها دور رئيس في العملية التعليمية وبالتالي في نتائجها, كنسب النجاح الجيدة, ونسبة المترفعين(المنقولين) إلى الصف الأعلى .....الخ, مما دعانا إلى استنباط أسلوب كمي لحساب نسبة الطلاب المترفعين(المنقولين) من سنة دراسية الى سنة اعلى وذلك للمقارنة بين كفاءة كل من النظام الفصلي الحالي والنظام الفصلي المعدل، ومن اهم النتائج التي تم التوصل اليها هي:1 ـ بلغت نسبة ترفع(انتقال) الطلاب من السنة j الى السنة الاعلى j+1 وفق النظام الفصلي الحالي ما يقارب 60% .2. بلغت نسبة ترفع(انتقال) الطلاب من السنة الدراسية j الى السنة الاعلى j+1 وفق النظام الفصلي المعدل 89.64%. Considering that the educational process is a system of processes that are interconnected with each other and participate in the occurrence range of factors, affect and are affected by each of which has the role of the president in the educational process and therefore in the results, as percentages of good success, the proportion of Almitrfien (transferred) to the top grade ..... etc., which invited us to devise a quantitative method to calculate the ratio of students Almitrfien (transferred) from one academic year to a year high, and the comparison between present quarterly system efficiency and the system's quarterly average, and the most important results that have been reached are:1. percentage lift (transmission) students of the school year j to year, the Supreme j + 1 according to the present quarterly system nearly 60%.2. accounted lift (transmission) students of the school year j to year, the Supreme j + 1 according to the quarterly system 89.64% average.